Kepemimpinan Religio-Paternalistik Kiai terhadap Lingkungan Sosial Santri di Pondok Pesantren Al-Muhajirin Ilallah Tambakberas Jombang - Karim, Moch Lukman; Ashoumi, Hilyah (JoEMS (Journal of Education and Management Studies), 2025)
This research aims to examine the religio-paternalistic leadership style adopted by the kiai (Islamic cleric) in Islamic boarding schools (pondok pesantren) and its relationship with the phenomenon of bullying, which has become increasingly common in several boarding schools recently. Bullying cases in pesantren, particularly those involving physical and psychological violence among students, have raised significant concern due to their high frequency and negative impact on student character development. This study employs a qualitative approach with a case study design at Al-Muhajirin Ilallah Islamic Boarding School. Data collection techniques include in-depth interviews with the kiai, senior and junior students, participatory observation, and document analysis. The findings reveal that the religio-paternalistic leadership style employed by the kiai creates a strong bond between the kiai and the students, grounded in religious values and profound respect for the kiai figure. Although this leadership style successfully fosters student discipline and loyalty, its somewhat authoritarian approach also has the potential to limit student initiative and creativity. Additionally, bullying cases in pesantren are related to the hierarchy of seniority and a lack of effective institutional oversight. In conclusion, the kiai’s religio-paternalistic leadership positively impacts student character and discipline; however, it needs to be complemented with a more inclusive institutional management system to prevent bullying and encourage students' holistic development.